2009
DOI: 10.1155/2009/206506
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Tiotropium as a Steroid‐Sparing Agent in Severe Asthma

Abstract: People with severe asthma account for 5% to 10% of all asthmatic patients; however, this small group uses the majority of health care resources. Novel methods are needed to cope with the burden that this minority of patients places on the health care system. A severe asthma clinic patient, who was monitored through the University of Alberta's Virtual Asthma Clinic (Edmonton, Alberta) is presented. Despite optimization of his disease and individualized asthma education (provided by a certified asthma educator),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Recently, several studies have suggested the efficacy of anticholinergics in severe asthma,32,33 and interest about the use of long-acting anticholinergics (e.g. tiotropium bromide) for asthma have increased.…”
Section: Interaction Between Genetic Variations and Anticholinergicsmentioning
confidence: 99%
“…Recently, several studies have suggested the efficacy of anticholinergics in severe asthma,32,33 and interest about the use of long-acting anticholinergics (e.g. tiotropium bromide) for asthma have increased.…”
Section: Interaction Between Genetic Variations and Anticholinergicsmentioning
confidence: 99%
“…[9][10][11][12] More importantly, Peters et al 13 recently demonstrated in patients with mild-to-moderate asthma uncontrolled with only low-dose ICSs that the addition of tiotropium yielded superior improvements in morning and evening PEF, prebronchodilator FEV 1 , symptoms, and asthma control days compared with doubling the dose of ICSs. In the same study the use of tiotropium was found not to be inferior to salmeterol.…”
mentioning
confidence: 99%
“…15 In 2009, a case report was published describing a 43-year-old man with adult-onset atopic asthma with an initial PEF rate of 450 L/min. 16 The patient remained symptomatic despite his regimen of daily oral corticosteroids, highdose ICS plus LABA, a leukotriene modifier, and a quickrelief SABA. He was given tiotropium 18 µg inhaled once daily.…”
Section: Clinical Trials and Case Studiesmentioning
confidence: 97%